Tratamiento Contable de la cuenta anticipos a funcionarios públicos del gobierno Autónomo Descentralizado Municipal del cantón Urdaneta - Valarezo Justillo, Xiomara Katherine (2020)
The present case study is carried out with real data and situations of the Municipal Autonomous Decentralized Government of the Canton Urdaneta created on October 11, 1913, it is a public administrative institution in charge of ensuring the well-being of its people by making correct use of the public resources provided by the state and those generated from its self-management. The case study was developed applying the method of direct observation under the research line financial information management and social commitment, where the account 1.1.2.01.01 Salary advances to Public Servants was analyzed, in which anomalies were identified in registration, and control of it. Where it was determined that the account was not properly monitored since the relevant discounts were not made, the balances were not verified and advances were made to the servers outside of what is allowed by regulatory standards